ANALISIS TERHADAP ASPEK HUKUMAN KESALAHAN JENAYAH DALAM KANUN NEGERI LINGGA: An Analysis of Criminal Penalties in the Kanun Negeri Lingga - Hamrie, Fatimah; Bujang, Saimi (Jurnal Syariah, 2025)
This study examines the content of the Kanun Negeri Lingga (KNL) manuscript, an Undang-Undang Melayu Lama (UML) legal text that demonstrates the existence of a structured and functioning Islamic legal system in Sarawak prior to the colonial era. Although several UML texts have been identified in Sarawak, in-depth research on KNL remains limited. Therefore, this study aims to analyse the punitive aspects of Islamic criminal offences outlined in KNL—a field that has received little scholarly attention, especially in Sarawak’s context. A qualitative descriptive approach was employed, using library research and document analysis methods. The data analysis was conducted in several systematic stages. These stages were: (i) preparation and understanding of the text, (ii) comprehensive reading of KNL, (iii) data coding, (iv) thematic classification, and (v) interpretation of the content based on the Islamic legal framework. The findings reveal that KNL details punishments for offences such as apostasy (murtad), adultery (zina), theft, false accusation (qazaf), retribution (qisas) and discretionary punishments (ta’zir), in accordance with Shariah principles. These provisions reflect an organised and functional implementation of Islamic criminal law, serving as an early foundation for understanding the Islamic legal system in Sarawak. The study’s findings also contribute to reinforcing the influence and relevance of KNL in shaping the contemporary Islamic legal framework in Sarawak.